Radiation therapist (RTT) perspectives on developing image-guided radiotherapy (IGRT) protocols for reirradiation - Aileen Duffton; Lynsey Devlin; Aoife Williamson; Derek Grose; Eilidh Tolmie; Linda MacLaren; Sharon McFadden; Rebecca Muirhead (Technical Innovations & Patient Support in Radiation Oncology)
Introduction: Prospective studies on reirradiation are limited, with most available data being retrospective, resulting in challenges in standardising protocols, interpreting outcomes, and facilitating informed patient decisions. Advanced radiotherapy planning and delivery have increased treatment possibilities for complex cases, including reirradiation. However, considerable gaps and variability in reirradiation image-guided radiotherapy (IGRT) and treatment delivery exist. The aim of this work was to identify ways to optimise reirradiation IGRT protocols based on RTT feedback. Methods: A quantitative and qualitative service improvement approach was selected, using a plan, do, check approach. RTT participants working in a single RT centre participated in focus group/nominal group technique sessions. Sessions were used to generate themes, challenges and solutions, which were then scored using Likert scale scoring criteria by all participants. Results: Eleven IGRT team members each with > 6 years experience participated in the sessions, (4 senior specialist clinical RTT, 2 team leader specialist RTT, 2 IGRT specialist RTT, 1 consultant RTT and 2 research RTT). Eight themes, 19 challenges and 35 solutions were identified. These included communication challenges and multi-professional team (MPT) involvement, RTT role and development, clinical information and treatment intent, standards and guidelines, individualised approach, technical planning considerations, imaging and verification techniques, and anatomical site-specific considerations. Conclusion: The themes identified provide valuable insights that will inform future IGRT processes and inform future research collaborations on an international level, working towards improving reirradiation treatment for patients who would benefit. There are many opportunities for the RTT within the MPT, and advanced practice (AP) can provide the framework required to develop this for the benefit of patients.